Recommendations for Intensive Care Management in Small Animals Following Anaesthesia - Dyson, Doris H.; Mathews, Karol (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Intensive care management can be provided in a small animal facility by centralisation of emergency and monitoring equipment. Good communication between all personnel involved in the case ensures that staff are prepared for complications that could arise related to recovery from anaesthesia.
Keywords: Intensive care; anaesthesia; analgesia